FORMATION OF LITERARY CREATIVITY AMANA TOKTOGULOVA (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
This article analyzes the formation of the work of the poet, translator and critic A.Toktogulov.
Keywords: literary creativity, formation, poetry, literary translation, literary criticism.